2017
DOI: 10.15252/embr.201642825
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of RFCCtf18 reveal a novel chromatin recruitment role for Dcc1

Abstract: Replication factor C complexes load and unload processivity clamps from DNA and are involved in multiple DNA replication and repair pathways. The RFCC tf18 variant complex is required for activation of the intra‐S‐phase checkpoint at stalled replication forks and aids the establishment of sister chromatid cohesion. Unlike other RFC complexes, RFCC tf18 contains two non‐Rfc subunits, Dcc1 and Ctf8. Here, we present the crystal structure of the Dcc1‐Ctf8 heterodimer bound to the C‐terminus of Ctf18. We find that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…We show this is achieved through an unusual protein–protein mechanism that utilizes flexible electrostatic interfaces to enable high binding plasticity. These low-specificity electrostatic patches explain why it was previously thought that the Ctf18-1-8 complex binds to DNA ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…We show this is achieved through an unusual protein–protein mechanism that utilizes flexible electrostatic interfaces to enable high binding plasticity. These low-specificity electrostatic patches explain why it was previously thought that the Ctf18-1-8 complex binds to DNA ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 94%
“…In an EMSA supershift assay, wild-type Ctf18-1-8 saturated Pol2 CAT -DNA at the lowest tested concentration of 125 nM (Figure 2B ). Ctf18-1-8 alone weakly binds DNA ( 27 , 28 ), but control experiments showed that this is not the cause of any supershifted bands ( Supplementary Figure S1F ). The Dcc1-3A and Ctf18-RAA variants showed a clear binding defect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prototypical member (Rfc1-RFC) is essential for all replication and repair processes, whereas Rad24-RFC is involved in the DNA-damage checkpoint response 8-10, and Elg1-RFC is involved in proliferating cell nuclear antigen (PCNA) unloading 11 and genomic stability 12-14. CTF18-RFC was originally identified in screens for chromosome mis‐segregation 15-17 in budding yeast ( Saccharomyces cerevisiae ) and is important for the establishment of sister-chromatid cohesion 16, 18 and the activation of the replication-stress checkpoint 15, 19, 20. During DNA-replication processes, CTF18-RFC assists DNA replication by loading the PCNA clamp onto the DNA 21-23, but the depletion of CTF18-RFC reduces the speed of replication-fork traversal 24 and results in defects in telomere metabolism 25 and DNA-repair processes 26, 27.…”
Section: Introductionmentioning
confidence: 99%